2020
DOI: 10.21203/rs.3.rs-21081/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long noncoding RNA MAPKAPK5-AS1 promotes colorectal cancer progression by cis-regulating the nearby gene MK5 and acting as a let-7f-1-3p sponge

Abstract: Background: Long noncoding RNAs (lncRNAs) are considered critical regulators in cancers; however, the clinical significance and mechanisms of MAPKAPK5-AS1 (hereinafter referred to as MK5-AS1) in colorectal cancer (CRC) remain mostly unknown. Methods: In this study, quantitative real-time PCR ( qPCR ) and western blotting were utilized to detect the levels of MK5-AS1, let-7f-1-3p and MK5 (MAPK activated protein kinase 5) in CRC tissues and cell lines. The biological functions of MK5-AS1, let-7f-1-3p and MK5 in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that lncRNAs can be broadly divided into cis-acting lncRNAs, affecting the expression or chromatin state of nearby genes, and trans-acting lncRNAs that perform various functions in the cell [20,21,31,32]. Considering that EGFR-AS1 is transcribed on the opposite strand of EGFR, we analyzed the RNA sequence base pairing between EGFR-AS1 and EGFR mRNA.…”
Section: Maintenance Of Egfr Mrna Stability By Egfr-as1 Via Complementary Bindingmentioning
confidence: 99%
“…Previous studies have demonstrated that lncRNAs can be broadly divided into cis-acting lncRNAs, affecting the expression or chromatin state of nearby genes, and trans-acting lncRNAs that perform various functions in the cell [20,21,31,32]. Considering that EGFR-AS1 is transcribed on the opposite strand of EGFR, we analyzed the RNA sequence base pairing between EGFR-AS1 and EGFR mRNA.…”
Section: Maintenance Of Egfr Mrna Stability By Egfr-as1 Via Complementary Bindingmentioning
confidence: 99%
“… 19 Moreover, Yang et al indicated that MAPKAPK5-AS1 promotes colorectal cancer progression by cis-regulating the nearby gene MK5 and acting as a let-7f-1-3p sponge. 20 However, whether MAPKAPK5-AS1 participates in thyroid cancer tumorigenesis and progression is still unknown.…”
Section: Introductionmentioning
confidence: 99%